2020
DOI: 10.2196/22457
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Compliance With Personal Preventive Measures Among Chinese Factory Workers at the Beginning of Work Resumption Following the COVID-19 Outbreak: Cross-Sectional Survey Study

Abstract: Background Maintaining compliance with personal preventive measures is important to achieve a balance of COVID-19 pandemic control and work resumption. Objective The aim of this study was to investigate self-reported compliance with four personal measures to prevent COVID-19 among a sample of factory workers in Shenzhen, China, at the beginning of work resumption in China following the COVID-19 outbreak. These preventive measures included consistent wea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
82
4
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(94 citation statements)
references
References 21 publications
5
82
4
3
Order By: Relevance
“…As compared to frontline workers, management staff were more willing to receive a COVID-19 vaccination. Studies among factory workers have shown that management staff were more likely to adopt personal measures to prevent COVID-19 [28]. Having children was associated with a lower intention to receive a COVID-19 vaccination; future studies should explore whether there are any specific barriers for parents.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As compared to frontline workers, management staff were more willing to receive a COVID-19 vaccination. Studies among factory workers have shown that management staff were more likely to adopt personal measures to prevent COVID-19 [28]. Having children was associated with a lower intention to receive a COVID-19 vaccination; future studies should explore whether there are any specific barriers for parents.…”
Section: Discussionmentioning
confidence: 99%
“…Random intercept models were used to allow the intercept of the regression model to vary across study sites, which could account for intracorrelated nested data. Multilevel logistic regression models are commonly used in studies with similar sampling methods [28,56]. A univariate two-level logistic regression model first assessed the significance of the association between each of the background characteristics and the dependent variables.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… In the experiment, “the speed of vaccine acquisition” and “the performance of COVID-19 containment” were two critical factors to assess the robustness of a factory to the COVID-19 pandemic, which was similar to Tesla’s practice of reopening its factories in China and USA [ 78 ]. The two regions have performed well in containing the COVID-19 pandemic and/or developing vaccines [ 79 , 80 ]. An existing method, the fuzzy extent analysis (FEA)-FWA method [ 81 ], was also applied to the collected data for comparison.…”
Section: Discussionmentioning
confidence: 99%